Minat Wirausaha, Konsep Diri dan Kreativitas - Rita Kusuma Eka Ananta; Djalali; Muhammad Farid (Jurnal Psikologi Tabularasa, 2014)
This research aimed to examine the relationship between self concept and creativity with students interest in entrepreneurship. The partisipants were class XII student SMKN 2 and 4 Madiun, totally 420 students. Date collection metod used scale interest in enterprenuer, self concept, CORE scale. Data analysis used was multiple regressions. Analytical result obtained by double regress F (59,840), p = 0,000 (p 0,01) which means that self concept and creativity have a significant relationship with interest in enterprenuership. The result of correlation analysis between self concept by showing interest in enterpreneurship with t (9,580), p = 0,000 (p 0.05) which means there was a very significant positive correlation between self concept and interest in enterprenuership.The result of correlation analysis between creativity and interrest entreprenuership showed t (2,012) with p = 0,046 (p 0.05) which means there was significant positive correlatioan between creativity and interest in enterprenuership.